Pulmonary hypertension in congenital heart disease of children - Randriamanga, Radohery Lovasoa; Rakotoarivelo, Fanjaharimbola Cynthia; Rakotoarisoa, Lalaina Andonirina (International Journal of Contemporary Pediatrics, 2024)
Background: Pulmonary arterial hypertension is the dreaded complication of congenital heart disease with left-right shunt. The aim of this study was to describe the epidemio-clinical aspects of PAH associated with congenital heart disease. Methods: This was a retrospective descriptive multicentre study over a 2-year period (1 January 2020 to 31 December 2021) conducted in three University Hospitals in Antananarivo. Hospitalized children with congenital left-right shunt heart disease were included. Results: A total of 74 cases were recruited. The sex ratio was 0.7. The mean age of the children was 10.9 (SD=18.2) months. The mean age of onset of heart disease was 8 (SD=13.6) months. Heart disease was dominated by ventricular septal defect (51.3%), patent ductus arteriosus (39.2%), and atrioventricular canal (8.1%). PAH was encountered in 49 cases (66.2%). The majority of children with PAH were under 12 months of age (71.4%) and malnourished (70.2%). According to the type of heart disease, PAH was encountered in all complete CAVs, in 76.3% of CIVs and in 55.2% of PCAs. Eseinmenger’s syndrome was present in 4% of cases, and the death rate was 20.3%. Conclusions: Improved management of children with congenital heart disease is needed, both in terms of diagnosis and surgical treatment, to prevent the onset of PAH.